ANALYSIS OF THE INFLUENCE OF POOR CULTURE, NUMBER OF FAMILY MEMBERS, AND WORK SKILLS ON POVERTY GAPS IN ABANG DISTRICT - Ni Putu Meira Sri Widiyantari; I Gusti Wayan Murjana Yasa (Adisam Publisher, 2025)
Poverty is a situation where individuals or groups of men and women are unable to fulfill their basic rights to develop and maintain a dignified life. This research aims to determine the influence of several factors such as poor culture, number of family members and work skills on the poverty gap in Abang District. This research was carried out in Karangasem Regency, precisely in Abang District, in May 2024 until completion. The method used is observation and interviews. The sample determination method uses non- probability sampling and purportive sampling so that respondents are selected deliberately based on considerations by taking the entire sample of 100 samples. The data obtained was then processed tabulatedly and continued with descriptive analysis tests, moderated regression analysis, classical assumption tests, simultaneous influence (F-test), and partial influence tests (t-test). The research results found that poor culture, number of family members, work skills and perceptions of poverty conditions simultaneously have a significant influence on the poverty gap in Abang District. Poor culture and work skills partially have a positive and significant effect on the poverty gap in Abang District. The number of family members partially has a negative and insignificant effect on the poverty gap in Abang District. Perception of poverty conditions as a moderating variable that strengthens the influence of work skills in Abang District.